4th International Pipeline Conference, Parts a and B 2002
DOI: 10.1115/ipc2002-27108
|View full text |Cite
|
Sign up to set email alerts
|

Coatings and Backfill System Optimisation

Abstract: Early consideration of geotechnical conditions in coating selection and backfill design could prove technically, economically and environmentally beneficial. In addition, bedding, padding and backfilling requirements are not specified on a project specific basis and the current methodology for design, engineering and construction does not allow optimisation of the coating and backfill system. This paper is intended to review the financial and technical issues that need to be considered when selecting external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rock shield materials or imported or processed bedding and padding materials are often employed to prevent impact, penetration and abrasion damage, in poor ground conditions. Previous work 6 has indicated that FBEs require the padding and bedding materials to have a particle size of less than 10 mm to prevent impact damage during backfilling, and/or penetration and abrasion damage during service.…”
Section: Discussionmentioning
confidence: 99%
“…Rock shield materials or imported or processed bedding and padding materials are often employed to prevent impact, penetration and abrasion damage, in poor ground conditions. Previous work 6 has indicated that FBEs require the padding and bedding materials to have a particle size of less than 10 mm to prevent impact damage during backfilling, and/or penetration and abrasion damage during service.…”
Section: Discussionmentioning
confidence: 99%